Integration of ANP and QFD for Sustainable Supplier Selection in the Chemical Industry Supply Chain - Nicky Afrillia (Universitas Kristen Petra dan Ikatan Sarjana Ekonomi Indonesia Cabang Surabaya, 2026)
In response to global demands for sustainable business practices, chemical industry companies such as PT XYZ are required to implement procurement strategies that are not only efficient but also environmentally and socially responsible. This study aims to analyze the strategic role of the supply chain in supporting sustainable supplier selection, identify and prioritize sustainability criteria in the transportation supplier selection process, and develop a comprehensive decision-making approach by integrating the Analytic Network Process (ANP) and Quality Function Deployment (QFD) methods. The ANP method was applied to address the complexity of interdependent relationships among criteria, resulting in the highest priorities being placed on Green Transportation, Financial Capability, and Social Responsibility. Subsequently, the ANP results were integrated into the QFD method to translate customer sustainability requirements into supplier technical characteristics. The findings from the House of Quality indicate that the top-priority technical requirement is the use of environmentally friendly transport vehicles supported by alternative fuel infrastructure.